2021
DOI: 10.1136/bmjopen-2020-047553
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcomes of twin pregnancies in Botswana: a national birth outcomes surveillance study

Abstract: ObjectivesThis study aims to evaluate the prevalence and outcome of twin pregnancies in Botswana.SettingThe Tsepamo Study conducted birth outcomes surveillance at 8 government-run hospitals (~45% of all births in Botswana) from August 2014 to June 2018 and expanded to 18 hospitals (~70% of all births in Botswana) from July 2018 to March 2019.ParticipantsData were collected for all live-born and stillborn in-hospital deliveries with a gestational age (GA) greater than 24 weeks. This analysis included 117 593 si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Our findings were similar to those from other studies showing that twins received more antenatal steroids and were more likely to be delivered by caesarean section, be conceived by ART and be born at a tertiary perinatal centre [ 1 , 5 , 7 10 ]. Although our study found that twins conceived by ART are substantially higher than singletons (39.5% for twins, 7.3% for singletons), the mortality of twins was slightly higher than that of singletons.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings were similar to those from other studies showing that twins received more antenatal steroids and were more likely to be delivered by caesarean section, be conceived by ART and be born at a tertiary perinatal centre [ 1 , 5 , 7 10 ]. Although our study found that twins conceived by ART are substantially higher than singletons (39.5% for twins, 7.3% for singletons), the mortality of twins was slightly higher than that of singletons.…”
Section: Discussionsupporting
confidence: 91%
“…Over the past decade, the rate of very preterm twins has been increasing worldwide mainly due to the development of assisted reproductive technology (ART) and increased maternal childbearing age [ 1 7 ]. Data from the Australian and New Zealand Neonatal Network showed that the incidence of twins in extremely preterm infants increased from 21.6% in 1995–1999 to 25.6% in 2005–2009 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twin gestation and multigravida status were more frequently associated with pregnancy loss in the general population; such associations were previously noted. 33 , 34 , 35 …”
Section: Commentmentioning
confidence: 99%
“…With the liberalization of the fertility policy and the widespread application of assisted reproductive technology, the incidence of twin pregnancies has gradually increased, which is considered to be 1 of the main factors that increase the incidence of maternal complications including hypertensive disorders, anemia, postpartum hemorrhage, and maternal death. [ 1 ] Twin pregnancies are universally considered to be “high risk.” Compared to singleton pregnancies, twins are also more likely to be born preterm and to have restricted growth in utero, thereby increasing their risk for intrauterine demise and neonatal mortality. [ 1 ] Higher risk of fetal death, preterm delivery and growth restriction in monochorionic diamniotic twins (MCDAs) is occured compared with dichorionic diamniotic twins (DCDAs).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Twin pregnancies are universally considered to be “high risk.” Compared to singleton pregnancies, twins are also more likely to be born preterm and to have restricted growth in utero, thereby increasing their risk for intrauterine demise and neonatal mortality. [ 1 ] Higher risk of fetal death, preterm delivery and growth restriction in monochorionic diamniotic twins (MCDAs) is occured compared with dichorionic diamniotic twins (DCDAs). [ 2 ] Birth weight discordance (BWD) is 1 of the major determinants of perinatal outcomes in twins, with an associated increased risk of perinatal mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%